Pengembangan Perangkat Pembelajaran Biologi Berbasis Konstruktivisme Berdasar Teori Sosial Vygotsky di Sekolah Menengah Atas - Amin, Astuti Muh. (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2012)
DOWNLOAD PDFThe aims of study to determine the validity, practicality, and effectiveness of biology-based learning device based on the theory of social constructivism Vygotsky in Senior High School. This study included the type of research development. The development of learning device apply learning development procedure 4-D model which consists of define, design, develop, disseminate step. Results of analysis of research data suggests that the biology of learning Â devices Â based on the theory of social constructivism Vygotsky in Senior High School achieved the criteria of quailty, they are (1) validity where the validity of the lesson plan reach average 3.77 (very valid category), the validity score of the students book 3.75 (very valid category), and the validity average score of the students worksheet is 3.78 (very valid category). (2) the practicality, where rationally the theory is stated that sitable to be used by experts and practitioners based on the score of validity which very valid category and in real terms in the field has been applied with an overal average of implementation 3.81 (very god implemented category). (3) effectiveness, in which the ability of teachers to manage learning with a value of 3.65 (very high category), the activity levels of students with an ideal time activity, the responses of students with positive responses, and learning test results reached with the level of mastery classically achieve 88.89% mastery. Key word: Constructivism, 4-D model, Vygotsky.